Molecular Dynamics Simulation and Structural Insights into The SMN1 Protein Involved in the Pathogenesis of Spinal Muscular Atrophy - Bagga, Pankaj; Singh, Sudhakar; Ram, Gobind; Kapil, Subham; Eerapagula, Ramesh; Puri, Punit; Kumar, Jitender; Sheikh, Imran (Journal of Neonatal Surgery, 2025)
Spinal muscular atrophy (SMA) is an an autosomal recessive inherited neuromuscular condition distinguished by the deterioration of alpha motor neurons within the spinal cord. This degeneration leads to a gradual onset of muscle weakness and paralysis primarily affecting muscles close to the body's center. The SMA is categorized into four severity grades (SMA I, SMA II, SMA III and SMA IV) determined by the age of onset and the level of motor function attained. This condition arises from homozygous mutations in the survival motor neuron 1 (SMN1) gene, with diagnostic tests typically revealing homozygous deletion of SMN1 exon 7 in the majority of patients. Herein, we have applied bioinformatics approaches to predict the structure of SMN1 protein (using AlphaFold, I-TASSER and RoseTTAFold), structure validation (PSVS v1.5, PROCHECK and ProSA-web) and molecular dynamics (MD) simulation using GROMACS 2022.3 at 100 ns (nanoseconds) to analyze the Root Mean Square Deviation, Root Mean Square Fluctuation, and Radius of Gyration. MD results clearly indicate that RoseTTAFold predicted structure of SMN1 is highly stable and consistent.